Synthesis and characterization of α-Fe2O3/polyaniline nanotube composite as electrochemical sensor for uric acid detection - Mahmoudian, Mohammad Reza; Basirun, Wan Jefrey; Sookhakian, Mehran; Woi, Pei Meng; Zalnezhad, Erfan; Hazarkhani, Hassan; Alias, Yatimah (Elsevier, 2019)
We report the synthesis of α-Fe2O3/polyaniline nanotube (PAn NTs) composite as an electrochemical sensor for uric acid (UA) detection. Field emission scanning electron microscopy (FESEM) indicates a hexagonal shape of the α-Fe2O3 while a nanotube morphology of the PAn. Impedance spectroscopy results confirm a significant decrease in the charge transfer resistance of the glassy carbon electrode (GCE) modified with α-Fe2O3/PAn NTs due to the presence of PAn NTs. The results show that the increase in the conductivity of α-Fe2O3 in the presence of PAnNTs could improve the catalytic performance of α-Fe2O3/PAn NTs composite, compared to the pure α-Fe2O3 nanoparticles. From differential pulse voltammetry, a linear working range for the concentration of UA between 0.01 µM and 5 µM, with a LOD of 0.038 µM (S/N = 3) was obtained. The sensitivity of the linear segment is 0.433 μA µM−1. The reliability of the modified electrode towards the detection of UA was investigated in the presence of interfering acids such as ascorbic acid, citric acid and succinic acid.